Pengaruh Jenis dan Jumlah Sumbu Pada Hidroponik Sistem Wick Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) Varietas Maritima - Puji Lestari, Diyah Ayu; Muharam, Muharam; Subardja, Vera Oktavia (JURNAL AGROPLASMA, 2023)
Lettuce is one of the vegetable crops which has good economic value and good market prospects to be cultivated by Indonesian people. We know we had a lot of switched agricultural land that it makes our agricultural land is being decreased. A solution of this problem is usingthe hydroponic technique with wick system inside. The purpose of this research is to determine the effect of te types combination and wick amount of the highest hydroponic wick system, and to obtain the highest growth and yield of Maritima variety green lettuce (Lactuca Sativa L.). A method which used in this research is Randomized Block Design (RAK) Single Factor consisting 9 treatments and 3 replications. Treatment A (Flannel Fabric + 2 Axis), B (Flannel Fabric + 3 Axis),C (Flannel Fabric + 4 Axis), D (Wool Fabric + 2 Axis), E (Wool Fabric + 3 Axis), F (Wool Fabric + 4 Axis),G (Coconut Coir + 2 Axis), H (Coconut Coir + 3 Axis) and I (Coconut Coir + 4 Axis). The impact of treatment being analyzed using the F test at a significant 5% level, to find out the best treatment it was continued with the Duncan Multiple Range Test (DMRT) at a 5% level. The results showed that the type and number of axes significantly affected the growth and development of lettuce (Lactuca Sativa L.). Treatment F (Wool Fabric + 4 Axis) gave the highest yield of plant height at 42 hst was 18.80 cm, number of leaves at 42 hst was 14.53 leaves, leaf area at 42 hst was 154.54 cm2and weight fresh fruit per plant at 42 hst was 137.28 g.Key words: Lettuce, Axis Type, and Number of Axis.Â